2007
DOI: 10.1111/j.1600-6143.2007.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Pneumococcal Vaccine in Renal Transplant Recipients—Three Year Follow‐up of a Randomized Trial

Abstract: Routine pneumococcal vaccination is recommended at regular intervals posttransplant. However, there is limited data on durability of vaccine response and the impact of vaccine type on antibody persistence. We determined the durability of response for patients enrolled in a randomized trial of conjugate (PCV7) versus polysaccharide (PPV23) pneumococcal vaccination. Response was defined as a twofold increase from baseline and a titer ≥0.35 lg/mL using a pneumococcal ELISA for seven serotypes (measured at 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 22 publications
4
49
2
1
Order By: Relevance
“…13 In kidney transplant patients vaccinated a mean of 1.2 years after transplant with either one dose of PCV7 or one dose of PPV23, the specific antibody levels had significantly decreased 3 years later, especially for pn4 and pn9V, and the durability of the response did not depend on the type of the vaccine but only on the level of the initial response. 14 In HSCT patients, due to the lack of data in the literature, the more recent guidelines do not give any recommendation on antipneumococcal immunization after 12 months posttransplant. 5 Our study is the first with a long follow-up of an homogeneous cohort of patients vaccinated 10 years ago according to the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…13 In kidney transplant patients vaccinated a mean of 1.2 years after transplant with either one dose of PCV7 or one dose of PPV23, the specific antibody levels had significantly decreased 3 years later, especially for pn4 and pn9V, and the durability of the response did not depend on the type of the vaccine but only on the level of the initial response. 14 In HSCT patients, due to the lack of data in the literature, the more recent guidelines do not give any recommendation on antipneumococcal immunization after 12 months posttransplant. 5 Our study is the first with a long follow-up of an homogeneous cohort of patients vaccinated 10 years ago according to the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In the immunocompromised populations, this decline should be more frequent and more important, although precise data are lacking. After antipneumococcal vaccination in renal transplant recipients, it has been shown that one of the main determinant of the durability of the response is the level of the immediate immune response, rather than the type of the vaccine [31]. Individual assessments of vaccine-specific antibodies could certainly help for deciding to revaccinate, but these tests are not routinely available in many centers.…”
Section: Durability Of the Responsementioning
confidence: 96%
“…44 Because boosting is more effective in patients who are immunized before transplantation, all transplant candidates should undergo pneumococcal vaccination. 46 Furthermore, the American Society of Transplantation recommends routine pneumococcal vaccination every 3-5 years. 12 …”
Section: Pneumococcal Vaccinementioning
confidence: 99%